ANALISIS FAKTOR – FAKTOR KEIKUTSERTAAN IBU HAMIL TRIMESTER III TERHADAP PRENATAL YOGA: Analysis Factors of Participations Pregnant Mothers Third Trimester On Prenatal Yoga - Setiana Andarwulan; Anik Latifah; Yuni Khoirul Waroh (LPPM - STIKES Pemkab Jombang, 2022)
Indicators of success in providing obstetric and perinatal services can be seen from the maternal and perinatal mortality rates. Maternal and perinatal mortality rates in Indonesia are still quite high. One of the health services that is non-conventional and can provide benefits in the delivery process is prenatal yoga. Prenatal yoga is a combination of movements between the regulation of breath, mind and movement in a single unit. The purpose of this study was to determine the relationship between parity and the participation of pregnant women in the third trimester in participating in pregnancy exercise. The research design used was cross sectional with simple random sampling method. The number of respondents who follow prenatal yoga as many as 30 respondents. The research data was taken by giving a questionnaire which was then observed. Furthermore, data tabulation was carried out and tested with Chi Square. The results of the study obtained that most of the pregnant women who took part in prenatal yoga were 20 respondents (40%). The results of the chisqure rang test have a significance level of age p value = 0.001, parity p value = 0.026 and work p value = 0.012 with p value = 0.05 then H1 is accepted meaning that there is a significant relationship between the factors analyzed in the participation of prenatal yoga . In conclusion, H1 is accepted, which means that there is a relationship between age, parity and occupation with the participation of pregnant women in the third trimester in participating in prenatal yoga. It is hoped that health workers will further improve the provision of health education about non-conventional medicine so that mothers who will give birth will be better prepared physically and psychologically. Keywords : Parity, Prenatal Yoga, Pregnant Mother